Evaluation of Municipal Solid Wastes Based Energy Potential in Urban Pakistan - Siddiqi, Muhammad Mobin; Naseer, Muhammad Nihal; Wahab, Yasmin Abdul; Hamizi, Nor Aliya; Badruddin, Irfan Anjum; Chowdhury, Zaira Zaman; Akbarzadeh, Omid; Johan, Mohd Rafie; Khan, T.M. Yunus; Kamangar, Sarfaraz (MDPI, 2019)
Solid waste management needs re-evaluating in developing countries like Pakistan, which currently employs landfilling as a first option. Over time, increasing population will result in decreasing space for landfill sites, ultimately increasing the cost of landfilling, while increasing accumulated waste will cause pollution. Locating and preparing a sanitary landfill includes the securing of large sectors and also everyday activity with the end goal to limit potential negative impacts. Energy production from municipal solid waste (MSW) is a perceptive idea for large cities, such as Karachi, as waste, which is an undesirable output that adds to land and air pollution, is transformed into a vital source of energy. The current study strives to provide a destination to solid waste by evaluating the energy potential that waste provides for power generation by the process of incineration. A sustainable energy generation plant based on the Rankine cycle is proposed. This study evaluates the various landfill sites in the case study area to determine their sustainability for a waste to energy (WtE) plant. The implementation of the proposed plant will not only provide an ultimate destination to waste but also generate 121.9 MW electricity at 25% plant efficiency. Thus, the generated electricity can be used to run a WtE plant and meet the energy requirements of the residents. © 2019 by the authors.